SELF-ACCEPTANCE AND SOCIAL ANXIETY IN ADOLESCENTS: A CORRELATIONAL STUDY - Zulvana; Didik Susetiyanto Atmojo; Iva Milia Hani Rahmawati; Erni Rahmawati (Nursing Sciences Journal, 2025)
Social anxiety is a psychological disorder commonly experienced by adolescents, especially during the transition to adulthood. Self-acceptance is believed to influence the level of social anxiety in adolescents. This study aims to identify the relationship between self-acceptance and social anxiety in seventh-grade students at SMP Negeri 2 Plemahan. The type of research is a quantitative approach with a descriptive-analytic design and a cross-sectional approach was used. The sample consisted of 69 students selected through purposive sampling. The instruments used included the Social Anxiety Scale for Adolescents (SAS-A) and Berger’s Self-Acceptance Scale. Data were analyzed using Chi-Square tests. The results showed that the majority of respondents were female and aged 13. Most respondents exhibited moderate levels of both social anxiety and self-acceptance. A significant relationship was found between self-acceptance and social anxiety with a moderate relationship strength. Conclusion and suggestions in this research is increasing self-acceptance can be an effective strategy to reduce social anxiety in adolescents. It is recommended that schools develop counseling programs to support the enhancement of students' self-acceptance.